Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content:1. Women's work in the military sector and its impact on family relations – A descriptive study on a sample of families in Jeddah –Ms. Reem Abdulrahman Al-Zahrani, Ms. Ramiyah Khader Al-Rami, Dr. Samira Saad El-Din El-Maghribi2. Social Dominance in Saudi Narration, Sociological Approach in Selected NovelsMs. Shoroq Abdullah Althumairi3. Simulating The Temporal and Spatial Patterns of Urban Growth in Abha Using the Markov-CA Combined Statistical Model During The Period from 2000 to 2040Ms. Eman Mohammed Ali Alqahtani4. Housing at Risk of Collapse and its Effects on the Health Situation of Residents and Management Policies: The Case of the Old City of Salé in MoroccoDr. Nezha Arabi, Dr. Mohamed Aneflouss5. Evaluating the spatial suitability of primary schools for boys in the city of Makkah using multi-criteria geographic information systemsMs. Abdullah Abdul-Aziz Yamani, Dr. Morshed Muayoud Al-Salmi6. The transportation system and its role in the relations between urban centers and rural areas in the Inaoun Basin DepressionDr. Ali Neddama, Dr. Jaouad El-Bazoui, Dr. Abdelouahed Bouberria7. Improving Iraqi English Learners' Ability to Develop and Support Claims in Argumentative WritingMs. Dua’a Ali Tahir, Asst-Prof. Sawsan A. Qasim8. Cultural Identity Formations in Arabic Children's LiteratureDr. Rafea Saeid Yehia
Keywords: Journal of Human and Social Sciences